Upshot of Occupational Stress on Work Life Balance of Employees Working in Information Technology Organizations in Chennai - Kala, K.; Akbar Jan, N.; Subramani, A. K.; Banureka, R. (Prabandhan: Indian Journal of Management, 2017)
India’s information technology (IT) industry is the world’s largest sourcing destination, which accounts for approximately 67% of the US 124-130 billion market. The Indian IT industry provides direct employment to 3 million people and indirect employment to about 10 million. Most of the projects handled by the IT companies are for the companies located in developed countries; hence, the companies need to match their working hours and working style according to their international clients’ requirements. In order to fetch more projects, software companies promise their clients the delivery of the projects in the shortest span possible, which may lead to tough deadlines. This paper attempted to explore the impact of occupational stress on the work - life balance of employees working in IT organizations in Chennai city. This study followed descriptive research design with a sample of 600 employees from various IT companies located at DLF IT Park, Chennai. The data were analyzed through independent samples t - test and structural equation modelling approach. The outcome of the analysis revealed that there was an impact of occupational stress on the work-life balance of the employees. It was concluded that minimizing occupational stress may lead to better work-life balance.